PMA-qPCA: Accelerating the market release of high-quality Bradyrhizobium diazoefficiens inoculant - Mariana Cap; Camila Frydman; Antonella Galiñanes; Camila Aranguiz; Irina Faraco; Luisina Andriolo; Viviana Parreño; Marina Mozgovoj (PLoS ONE, 2025)
Traditional culture-based quantification of Bradyrhizobium diazoefficiens in inoculants presents significant limitations due to its labor-intensive and time-consuming nature. To address this limitation, we aimed to validate a propidium monoazide quantitative PCR (PMA-qPCR) assay as a rapid and reliable alternative for estimating Bradyrhizobium diazoefficiens counts in commercial inoculants. Key experiments optimized PMA concentration (50, 75 and 100 µM) to selectively inhibit DNA amplification from non-viable cells without interfering with viable cell signal. Assay´s efficiency, limit of detection and quantification, intra-assay repeatability and inter-assay reproducibility were determined. The assay demonstrated high efficiency (90–105%), a limit of detection (LOD) of 3.14 log CFU/mL, and a dynamic range from 8.74 to 3.14 log CFU/mL. Robust intra-assay repeatability (SD < 0.3) and inter-assay reproducibility (CV < 10%) were confirmed. The method successfully distinguished quarter-strength and 10-fold serial dilutions of viable bacteria, even in the presence of non-viable cells. Final validation against standard plate counting showed a strong linear correlation with an R² of 0.82. Crucially, this PMA-qPCR assay reduced processing time from 120 hours to just 5 hours, offering a significant improvement in turnaround time while maintaining strong agreement with the reference method. This study marks the first application of PMA-qPCR for Bradyrhizobium diazoefficiens quantification in inoculants, highlighting its potential as a high-throughput tool to enhance efficiency and precision for industrial batch-to-batch quality control.